Respuesta :
t + m = 26
m = t - 6
t + t - 6 = 26
2t - 6 = 26
2t = 26 + 6
2t = 32
t = 32/2
t = 16 <==== trevor has 16
m = t - 6
m = 16 - 6
m = 10.......marissa has 10
m = t - 6
t + t - 6 = 26
2t - 6 = 26
2t = 26 + 6
2t = 32
t = 32/2
t = 16 <==== trevor has 16
m = t - 6
m = 16 - 6
m = 10.......marissa has 10
Let Trevor = t, and Marissa = m
m + t = 26
m = t - 6
Plug in t - 6 for m
(t - 6) + t = 26
Simplify. Combine like terms.
2t - 6 = 26
Isolate the t. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS.
2t - 6 (+6) = 26 (+6)
2t = 32
2t/2 = 32/2
t = 16
Trevor sells 16 shirts.
Subtract 16 from 26
26 - 16 = 10
Marissa sells 10 shirts.
hope this helps